The level of political activism among voters in selected barangays in Palo, Leyte. - Reglo, Jerome C.; Tamboong, Karah Jane A. (Tacloban City Jerome C. Reglo [and] Karah Jane A. Tamboong, 2010)
Palo is a third-class municipality, considered as the seat of Roman Catholicism in the Province of Leyte. Palo may be situated at the center of a rural-urban continuum. Hence, it is a very ideal locale for the study of political activism. Political activism refers to the extent of one's participation in political processes. In the context of this research, political activism entails participation in politically-related, cause-oriented, campaign-oriented, and civic-oriented activities.
The authors conducted this descriptive study to determine the level of political activism of the voters in Palo, Leyte and how this level is influenced by the voters' socio-economic and demographic characteristics. The levels of political activism were expressed through arithmetic means. And the relationships between variables were measured using Spearman's rho and Contingency coefficient.
The results revealed that majority of the voters are females, aged between 18 to 25 years, married, Roman Catholic, have at least attended College, self-employed and earn 10,000 to 50,000 pesos annually. Overall, there is an average level of political activism among voters. But if the individual indicators of political activism are considered, it may be gleaned that there is a high level of political activism in terms of participation in politically-related activities but low levels in terms of participation in cause-oriented, campaign-oriented, and civic-oriented activities. The analyses suggest that the level of political activism is significantly correlated with age, highest educational attainment and annual income, while at the same time, highly associated with sex, civil status and occupation.
The findings of this study are important because they can shed light into the problem of democratic deficit in Palo.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science